Truth, Identity, Pluralism in Contemporary Society - Gandhi's Response - Bishwanath Sharma, Laimayum; Shantilata Devi, Thokchom (Tattva Journal of Philosophy, 2021)
This paper explores Gandhi’s attitude towards diversity of religions and examines as to how he attempted to bring inter-faith harmony. Religious diversity has been a topic of serious debate in the contemporary philosophical discourse on understanding religion. Religious pluralism is one of the approaches that deal with issues concerning the diversity of religions. It is believed that no single religion can make absolute claims about the nature of divine reality, its relation to man and the world. It stands in direct opposition to exclusivism, inclusivism and also to fundamentalism by denying that any one religion is the sole possession of the whole truth. Different religions seem to put forward different and incompatible interpretations about the nature of ultimate reality, about the modes of divine activity, the nature and destiny of the human race.